EVALUATION OF COASTAL SAFETY STRUCTURES IN MITIGATING WAVE OVERTOPPING: A LABORATORY SIMULATION APPROACH - Nur Aulia; Irawan Alham; Paharuddin Paharuddin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research evaluates the performance of coastal safety structures in mitigating wave runoff through laboratory-scale simulations. Pancana Beach in Barru Regency, South Sulawesi, was selected as the research site due to its vulnerability to wave-induced beach damage. To simulate wave conditions, a wave generator was designed using a 12-volt DC motor integrated into an acrylic wave bath. This research analyses the effectiveness of three types of coastal safety structures: reflectors, sea walls and sloping sea walls. Laboratory experiments measured the wave overflow volume for each type of structure under controlled conditions. The results showed that reflector-type structures achieved the highest efficiency in mitigating wave overtopping, with an average minimum overtopping value of 0.006 m³/ms. The findings emphasise the importance of selecting and designing appropriate coastal protection measures to minimise coastal erosion, protect coastal infrastructure and reduce risks to surrounding settlements. This study contributes valuable insights into the role of engineered structures in enhancing coastal resilience, especially for areas vulnerable to high wave energy.